2016
DOI: 10.5897/ajmr2016.7627
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal microorganism consideration and protein used in the metabolism of the ruminants: A review

Abstract: A great diversity of species of microorganisms are present in the rumen environmental with specific functions in the degradation of carbohydrates, protein and lipids. However, the knowledge of the interactions between the different species of microorganisms in the rumen ecosystem and their specific substrates were used to improve nutritional management and can increase production of meat or milk. A balanced nutritional management is very important. When inappropriate feedstuffs are used on diet formulation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 67 publications
1
13
0
4
Order By: Relevance
“…Gliricidia sepium on Rumen Fermentation The VFA content in rumen fluid can be used as a measure of the efficiency of the fermentation process in the rumen [42]. The results of statistical analysis showed that the treatment had no significant effect on the total amount of VFA, acetate, butyrate and valerate + isovalerate + isobutyrate.…”
Section: Effects Of Supplementing Ammoniated Rice Straw Withmentioning
confidence: 99%
“…Gliricidia sepium on Rumen Fermentation The VFA content in rumen fluid can be used as a measure of the efficiency of the fermentation process in the rumen [42]. The results of statistical analysis showed that the treatment had no significant effect on the total amount of VFA, acetate, butyrate and valerate + isovalerate + isobutyrate.…”
Section: Effects Of Supplementing Ammoniated Rice Straw Withmentioning
confidence: 99%
“…Oil seeds are known to have a high percentage (75% on average) of unsaturated fats (examples: oleic, linoleic, and linolenic acids) that are liquids at ambient temperature. They also have the added advantage of exerting an inhibitory effect on the growth of gram-positive bacteria (Malik et al, 2015;Valente et al, 2016Valente et al, , 2017. Excessive amounts of dietary lipids are known to have a negative…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the comparative protein quality of FF was a remarkable nutrient improvement, considering that the main energy source were mostly cellulotic and lignified carbohydrates. The capability of fungi to degrade cellulose and lignified carbohydrates, and accumulates protein in rumen [21], validates the authors' preference for the fungal consortium used as fermenters.…”
Section: Figure 1 Prevalence Of Yeast Isolated From the Fermented Comentioning
confidence: 94%